The Intellectual Conscience of Art - Ammann, Jean-Christophe; Balkema, Annette W.; Bonito Oliva, Achille; Bouman, Ole; Burgin, Victor; Cameron, Dan; Danto, Arthur C.; David, Catherine; Dercon, Chris; Elias, Willem; Groot, Paul; Hoet, Jan; et al. (Amsterdam / Atlanta : Editions Rodopi, 1996)
Art in Ruins ; Bijl, Guillaume ; Darboven, Hanne ; Demand, Thomas ; Dumas, Marlene ; Fleury, Sylvie ; Fortuyn/O'Brien ; Hirakawa, Noritoshi ; Hohenbüchler, Christine & Irene ; Huber, Thomas ; Kemps, Niek ; Kosuth, Joseph ; Levine, Les ; Mark, Arno Van der ; Mol, Pieter Laurens ; Persoon, Kars ; Pitz, Hermann ; Rummel, Michel ; Scholte, Rob ; Schouten, Lydia ; Schütte, Thomas ; Serafijn, Q.S. ; Steinbach, Haim ; Struycken, Peter ; Vanderheyden, JCJ ; Vertessen, Liliane ; Willems, Eldert ; Zaugg, Rémy ; van Elk, Ger
Engels
boek